Exploring the Role of Lipid-Binding Proteins and Oxidative Stress in Neurodegenerative Disorders: A Focus on the Neuroprotective Effects of Nutraceutical Supplementation and Physical Exercise - Giorgia Scarfò; Rebecca Piccarducci; Simona Daniele; Ferdinando Franzoni; Claudia Martini (MDPI AG, 2022)
The human brain is primarily composed of lipids, and their homeostasis is crucial to carry on normal neuronal functions. In order to provide an adequate amount of lipid transport in and out of the central nervous system, organisms need a set of proteins able to bind them. Therefore, alterations in the structure or function of lipid-binding proteins negatively affect brain homeostasis, as well as increase inflammation and oxidative stress with the consequent risk of neurodegeneration. In this regard, lifestyle changes seem to be protective against neurodegenerative processes. Nutraceutical supplementation with antioxidant molecules has proven to be useful in proving cognitive functions. Additionally, regular physical activity seems to protect neuronal vitality and increases antioxidant defenses. The aim of the present review was to investigate mechanisms that link lipid-binding protein dysfunction and oxidative stress to cognitive decline, also underlining the neuroprotective effects of diet and exercise.